Pengaruh Pembiasaan Pelafalan Teks Pancasila Setiap Pagi Terhadap Sikap Nasionalisme Siswa Kelas 3 Sekolah - Yesika Dwi Yuliana; Dya Ayu Agustiana Putri (PERMAI: Jurnal Pendidikan dan Literasi Madrasah Ibtida'iyah, 2025)
This study aims to determine the effect of reciting the Pancasila text every morning on the nationalistic attitudes of third-grade elementary school students. The study used a quantitative approach with a quasi-experimental design of the nonequivalent control group type. The research subjects consisted of two classes, namely the experimental class, which received the treatment of reciting the Pancasila text every morning, and the control class, which did not receive the treatment. The research instrument was a nationalism attitude questionnaire that had been tested for validity and reliability. Data were collected through pretest and posttest, then analyzed using the independent sample t-test with the help of the JAMOVI application. The results showed that there was no significant difference between the experimental group and the control group at the pretest. However, at the posttest, there was a significant difference, where the nationalistic attitudes of students in the experimental group were higher than those in the control group. These findings prove that the habit of reciting the Pancasila text every morning has a positive and significant effect on increasing the nationalistic attitudes of elementary school students. Therefore, the habit of reciting the Pancasila text can be used as an effective strategy in instilling nationalistic values from an early age in elementary schools.